ECONOMETRIC RESEARCH OF THE IMPACT OF THE GLOBAL FINANCIAL MARKET CONDITIONS ON THE INDEX RTS OIL & GAS - Vadim I. Mitrofanov (Статистика и экономика, 2016)
Based on the theory of cointegrationfor index RTS oil and gas for three time periods model of the relationship withthe factors of conjuncture in the globalﬁnancial market were built. Transformation of models under the inﬂuence of the global ﬁnancial and economic crisis was shown. The changes were explained from an economic point of view